FLEX (Fluorescence Explorer) mission: Observation fluorescence as a new remote sensing technique to study the global terrestrial vegetation state - J. Moreno; L. Alonso; J. Delegido; J.P. Rivera; A. Ruiz-Verdú; N. Sabater; C. Tenjo; J. Verrelst; J. Vicent (Revista de Teledetección, 2014)
FLEX (Fluorescence EXplorer) is a candidate for the 8th ESA’s Earth Explorer mission. Is the first space mission specifically designed for the estimation of vegetation fluorescence on a global scale. The mission is proposed to fly in tandem with the future ESA´s Sentinel-3 satellite. It is foreseen that the information obtained by Sentinel-3 will be supplemented with that provided by FLORIS (Fluorescence Imaging Spectrometer) onboard FLEX. FLORIS will measure the radiance between 500 and 800 nm with a bandwidth between 0.1 nm and 2 nm, providing images with a 150 km swath and 300 m pixel size. This information will allow a detailed monitoring of vegetation dynamics, by improving the methods for the estimation of classical biophysical parameters, and by introducing a new one: fluorescence. This paper presents the current status of FLEX mission in A/B1 phase and the different ongoing studies, campaigns and projects carried out in support of the FLEX mission.